2018
DOI: 10.1111/jcpp.12899
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: Emotional dysregulation in attention‐deficit/hyperactivity disorder – implications for clinical recognition and intervention

Abstract: Emotional symptoms in ADHD cause clinically significant impairments. Although there is a solid theoretical rationale for considering EI and DESR to be core symptoms of ADHD, there is no consensus about how to define these constructs sin a manner that would be specific to the disorder. An instrument to measure EI and DESR which demarcates them from irritability and other emotional symptoms could improve the accuracy of diagnostic criteria for ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
235
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(271 citation statements)
references
References 129 publications
(143 reference statements)
17
235
0
19
Order By: Relevance
“…There is increasing evidence of a close link between emotional symptoms and attention deficit hyperactivity disorder (ADHD) [1][2][3]. Several studies suggest that besides attentional and hyperactive-impulsive symptoms, emotional dysregulation (ED) is a core symptom of ADHD, both in childhood and adulthood [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence of a close link between emotional symptoms and attention deficit hyperactivity disorder (ADHD) [1][2][3]. Several studies suggest that besides attentional and hyperactive-impulsive symptoms, emotional dysregulation (ED) is a core symptom of ADHD, both in childhood and adulthood [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, others used cluster analysis to document that adult ADHD presents in these 2 forms. 21 Faraone et al, 22 in a careful review, concluded that there is "solid theoretical rationale" for regarding emotional impulsivity and deficient emotional self-regulation as "core symptoms of ADHD, " (p133) but how to implement this conclusion remains uncertain.…”
mentioning
confidence: 99%
“…An exhaustive review on ADHD has stressed that age largely influences findings on structural alterations (Faraone et al, 2019).…”
Section: Adhd Patients Show Neuropsychological Deficits In Attention Andmentioning
confidence: 99%